Liquidity risk impact on stock returns - Rapheedah Musneh; Mohd. Rahimie Abd. Karim; Caroline Geetha A/P B. Arokiadasan (Universiti Malaysia Sabah, 2020)
This study investigates the impact of liquidity risk on stock returns in the Malaysian stock exchange using the LCAPM model of Acharya and Pedersen. This research employed firm-level equity data involving 419 continuously listed firms in Bursa Malaysia from January 2000 to December 2018. The study employed LCAPM asset pricing model tested using Fama-Macbeth two-stage cross-sectional regression. The findings suggest that the covariance between stock illiquidity and the market return is not priced in the Malaysian stock market. While, the other explanatory variables are significant in explaining the cross-sectional variations of stock returns, but only two variables; the commonality in liquidity and net liquidity risks are correctly signed. The evidence is limited to Malaysian corporations listed in the Main Market of Bursa Malaysia. These findings show some new evidence on the application of the LCAPM model in the emerging markets by using the closing per cent quoted spread impact (CPQS Impact) of Chung and Zhang (2014) as a measure of illiquidity. This research provides new insights on LCAPM application in the Malaysian stock market.